Non-pharmaceutical interventions and risk of COVID-19 infection: survey of U.K. public from November 2020 - May 2021 - Nick A. Francis; Taeko Becque; Merlin Willcox; Alastair D. Hay; Mark Lown; Richard Clarke; Beth Stuart; Lucy Yardley; Michael Moore; Joëlle Houriet; Paul Little (BMC, 2023)
Abstract Introduction Non-pharmaceutical interventions (NPIs), such as handwashing, social distancing and face mask wearing, have been widely promoted to reduce the spread of COVID-19. This study aimed to explore the relationship between self-reported use of NPIs and COVID-19 infection. Methods We conducted an online questionnaire study recruiting members of the UK public from November 2020 to May 2021. The association between self-reported COVID-19 illness and reported use of NPIs was explored using logistic regression and controlling for participant characteristics, month of questionnaire completion, and vaccine status. Participants who had been exposed to COVID-19 in their household in the previous 2 weeks were excluded. Results Twenty-seven thousand seven hundred fifty-eight participants were included and 2,814 (10.1%) reported having a COVID-19 infection. The odds of COVID-19 infection were reduced with use of a face covering in unadjusted (OR 0.17 (95% CI: 0.15 to 0.20) and adjusted (aOR 0.19, 95% CI 0.16 to 0.23) analyses. Social distancing (OR 0.27, 95% CI: 0.22 to 0.31; aOR 0.35, 95% CI 0.28 to 0.43) and handwashing when arriving home (OR 0.57, 95% CI 0.46 to 0.73; aOR 0.63, 95% CI: 0.48 to 0.83) also reduced the odds of COVID-19. Being in crowded places of 10-100 people (OR 1.89, 95% CI: 1.70 to 2.11; aOR 1.62, 95% CI: 1.42 to 1.85) and > 100 people (OR 2.33, 95% CI: 2.11 to 2.58; aOR 1.73, 95% CI: 1.53 to 1.97) were both associated with increased odds of COVID-19 infection. Handwashing before eating, avoiding touching the face, and cleaning things with virus on were all associated with increased odds of COVID-19 infections. Conclusions This large observational study found evidence for strong protective effects for individuals from use of face coverings, social distancing (including avoiding crowded places) and handwashing on arriving home on developing COVID-19 infection. We also found evidence for an increased risk associated with other behaviours, possibly from recall bias.